Development of simple, rapid and sensitive detection assay for grouper nervous necrosis virus using real‐time loop‐mediated isothermal amplification. Issue 10 (30th July 2014) - Mekata, T; Satoh, J; Inada, M; Dinesh, S; Harsha, P; Itami, T; Sudhakaran, R
Abstract A quantitative rapid detection method based on loop‐mediated isothermal amplification has been developed for red‐spotted grouper nervous necrosis virus (RGNNV). The nested polymerase chain reaction (PCR) assay is the mainstream inspection of the brooder in the hatchery. In this study, a real‐time loop‐mediated isothermal amplification (LAMP) method has been applied for RGNNV detection, known as a high‐speed gene amplification procedure. Of the three temperatures (60 °C, 63 °C and 65 °C) attempted, it has been found that 63 °C is giving higher amplification from 11th minute onwards. Sensitivity analysis performed in comparison with real‐time polymerase chain reaction, reverse transcriptase PCR and nested RT‐PCR using various concentrations of template revealed that real‐time LAMP method is efficient in terms of cost and time consumption. Specificity analysis revealed that the method developed is specific to RGNNV, whereas it has sequence cross‐match with tiger puffer NNV giving advantage in detecting both the viruses. This method could be much efficient in analysing RGNNV in combination with TPNNV.